OPPORTUNITIES FOR INTEGRATION THE UKRAINIAN ELECTRICITY MARKET SPOT SEGMENTS TO MARKET COUPLING - PETRENKO, Daniil (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the market coupling impact on the Ukrainian electricity market spot segments and the electricity market as a whole, taking into account its current state, where all stakeholders are constantly dealing with war risks, with no adequate possibility to hedge its own security of supply. It is emphasized that today the Ukrainian government and the electricity market stakeholders with the support of European partners and experts, are actively working on the implementation of the European Union energy regulatory acts, in particular, regarding the integration of the Ukrainian electricity market spot segments to market coupling – Commission Regulation (EU) 2015/1222 of 24 July 2015 establishing a guideline on capacity allocation and congestion management. It is noted that the implementation of other European Union energy regulatory acts was in 2018, which resulted in adoption of Law of Ukraine “On the Electricity Market” that established a playing field for competition of different stakeholders on electricity market and possibility of end consumers to be a part of the market as well, which all in its entirety introduced the liberalized model of electricity market Ukraine from July 01, 2019. The current state of the electricity market was analyzed, according to which it was concluded that the electricity market is in the stage of formation and development, and also needs measures to further liberalize the market, increase liquidity, introduce the financial instruments market and debt repayment. In stages, taking into account the selected basic rules and principles of market coupling, a study of the market coupling impact on the Ukrainian electricity market was conducted. As a result, positive conclusions were obtained regarding the improvement of liquidity and competition; ensuring optimal distribution of interstate power transmission line capacities as well as of obtaining an additional source for the development of interstate power transmission lines. It is emphasized that integration to market coupling can become an incentive for electricity market participants to use financial hedging tools to reduce credit and market risks.